来日中国人看護師の日本での看護実践におけるやりがい - 王 妍蘊; 南部 泰士 (日本看護科学会誌, 2024)
要旨　目的：来日中国人看護師の日本での看護実践におけるやりがいを明らかにする．　方法：日本で看護師として働いている中国人看護師8名にインタビュー（半構造化面接法）を行い，質的帰納的に分析した．　結果：インタビューから6つのカテゴリーが導き出された．a【日本での看護実践を通じた専門的なスキルの習得】，b【患者とのケア・コミュニケーションを通じた信頼関係の構築】，c【日本の看護実践の多様な場に適応し看護師として貢献する】，d【患者・家族への将来の生活を考慮した退院支援での充実感】，e【日本人の仲間と安定した職場環境の中で得られる喜びと充実感】，f【日本での文化や暮らしから得られる安心感】であった．　結論：異なる文化や環境下での経験を通じて，看護実践の多様な場に適応し看護師として貢献するなど自己肯定感とやりがいをもたらしていた．専門的スキルの獲得や患者との信頼関係構築を含む様々な要素が中国人看護師にとって重要であることが明らかになった． 　Purpose: To clarify the rewarding of Chinese nurses in Japan in their nursing practice in Japan.　Methods: Semi-structured interviews were conducted with eight Chinese nurses working as nurses in Japan and analyzed qualitatively inductively.　Results: Six categories were derived from the interviews: a [Acquiring professional skills through nursing practice in Japan] b [Building trust through care and communication with patients] c [Adapting to various settings of nursing practice in Japan and contributing as a nurse] d [Fulfilment in supporting patients and families in their future lives e [Fulfilment in discharge support] e [Joy and fulfilment gained in a stable work environment with Japanese colleagues] f [Peace of mind gained from the culture and life in Japan].　Conclusion: Through their experiences in different cultures and environments, the participants adapted to the diverse settings of nursing practice and contributed as nurses, bringing a sense of self-affirmation and fulfilment. Various factors, including the acquisition of professional skills and building trusting relationships with patients, were found to be important for Chinese nurses.